Studi Populasi Elang Jawa (Spizaetus bartelsi Stresemann, 1924) di Gunung Salak, Taman Nasional Gunung Halimun â€“ Salak - Pribadi, Dharmawan Pandu (LPPM Universitas Negeri Jakarta, 2014)
Abstract Javan Hawk â€“ Eagles is an endemic raptor species in Java Island which is protected by the state and listed as endangered by IUCN and CITES Appendix II. The population of Javan Hawk - Eagles has been greatly reduced due to large-scale of illegal logging and forest destruction. The initial step that could be taken to preserve this species is to study the population in its natural habitat. Thus, studying the population of Javan Hawk - Eagles was the aim of this research. The research was conducted at Gunung Salak, Gunung Halimun â€“ Salak National Park in February to March 2011. Method used was explorative descriptive with look-down method on particular. Data were analyzed descriptively by describing the speciesâ€™ distribution map by using ArcGIS and ArcView GIS 3.3 softwares. The results showed that the eagle population consisted of 13 individuals with density and abundance values of 0.183 individuals/km2 (1 individual/6 km2) and 2. The values fell into â€œfew categoryâ€ and the distribution pattern was categorized as â€œuniformâ€. The eaglesâ€™ habitats were forest and hills at 797-1.383 meters above sea level although they are seen more often in forest. Key words: Gunung Salak, Javan Hawk â€“ Eagles, population